The Constitution, Taxation and "Avoiding Prolixity and Tautology" - Keith, Kenneth J (Victoria University of Wellington Law Review, 2022)
Sir Kenneth Keith reviews the efforts made over the past 35 years to improve the drafting of New Zealand legislation in general and tax law in particular.